A Tip to our Sunday Absentees cartoon, 1942 (1942)
1942 1939-1945 "A Tip to our Sunday Absentees cartoon, 1942" [HFR0081], 1942 This cartoon by Batt refers to an appeal made in March 1942 by John Marchbanks, General Secretary of the National Union of Railwaymen, urging railway workers to report for Sunday duties to help the war effort. The cartoon appeared in the Railway Review, 17 April, 1942.